The Determinants of Bank Risk- Taking in Ghana Mah - Osei-Asia, W. (My University, 2017)
vi ABSTRACT In their quest to making some considerable margins in order to stay relevant in the industry, banks undertake risks by managing the asset portfolio of their clients. In addition, they also face other risks such as credit risks, liquidity risks, operational risks and foreign exchange risks among others. In this regard, the study examined the determinants of the risk-taking behavior of some selected banks in Ghana. Bank specific and banking industry data were sourced from the financial reports of 10 sampled banks in Ghana whereas macroeconomic data was obtained from the Bank of Ghana for a 9-year period (2007-2015). The study made use of the panel regression model to examine the determinants of bank risks. The z-score was used as a measure of bank risk and the trend analysis revealed that GCB Bank, BBGL, and FBL had the highest risk above the overall mean on average. The study found banking industry and macroeconomic factors to have significant effects on bank risk. Under the banking industry factors, financial sector development was found to significantly influence bank risk. Interestingly, all the macro-level variables used in the study reported significant effects on bank risk. The study recommended that the government and the monetary authorities formulate favorable macroeconomic policies as well as stringent regulations on the risk portfolios of banks among others.
Keywords: Bank risk; -scores; GDP growth; managerial efficiency; industry competition; financial sector development